Juridical Analysis of Judicial Considerations in the Dispute Over Government-Owned Land in Surabaya Regarding Former Eigendom Verponding Land (Case Study of the Supreme Court's Revision Decision Number 1146 PK/Pdt/2025) - Ipung Salvota Mauludin; Wahyu Prawesthi; Yustino Aribawa (SEAN Institute, 2026)
Land disputes between colonial-era property claims and regional government asset inventories often trigger complex legal uncertainties in Indonesia. This study aims to analyze the consistency of the Supreme Court's legal considerations in Revision Decision Number 1146 PK/Pdt/2025 with national agrarian law principles and examine whether the decision violates the principle of verhandlungsmaxime (passive judge role) in protecting the assets of the Surabaya City Government. The research methodology employed is normative legal research with a statute approach, conceptual approach, and case approach. The findings indicate that the considerations in the Revision Decision are in full compliance with Law Number 5 of 1960 (UUPA) and Presidential Decree Number 32 of 1979, where land previously under Eigendom Verponding that was not converted by September 24, 1980, automatically became state land. As a result, the transfer of rights in 2006 to an individual was legally flawed based on the nemo plus iuris doctrine. Furthermore, the study concludes that the decision does not conflict with the verhandlungsmaxime principle, as the legal correction made by the judge reflects the principle of ius curia novit and the judicial obligation to protect regional assets for public interest. The research concludes that state sovereignty over remaining converted Western land rights is a key instrument in ensuring legal certainty in the management of regional assets.